2017
DOI: 10.5812/ircmj.44152
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Electronic Software and Training Booklet on Maternal Self-Confidence and Awareness About Newborn Care: A Randomized Controlled Clinical Trial

Abstract: Background: The use of a training booklet and electronic software has a special place due to lack of time and space constraints. Objectives: This study aimed to compare the effect of electronic software and training booklet on maternal self-esteem and awareness regarding newborn care in nulliparous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…It was calculated as 138 based on the study conducted by Jamalivand et al (17) on self-efficacy by considering SD = 3.0, d (Precision) = 0.5 and α = 0.05. Due to cluster sampling, and considering the design effect of 2.0, a 10% dropout rate was approximately calculated equal with 305.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…It was calculated as 138 based on the study conducted by Jamalivand et al (17) on self-efficacy by considering SD = 3.0, d (Precision) = 0.5 and α = 0.05. Due to cluster sampling, and considering the design effect of 2.0, a 10% dropout rate was approximately calculated equal with 305.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…In their study, Dilles et al, with the aim of comparing the effect of computer-based and booklet educational methods on the knowledge and self-care of cardiac patients, observed that there was no significant difference between the two groups in terms of knowledge and self-care scores [34]. Likewise, in the study by Jamalivand et al, which aimed at comparing the two methods on the knowledge and self-esteem of pregnant women, the results did not show significant differences between the two groups in terms of knowledge and self-esteem [35]. However, other studies have revealed contradictory results in comparing the effects of the two methods.…”
Section: Discussionmentioning
confidence: 89%
“…Education is a process that provides knowledge and motivation for people to adopt and maintain healthy behaviors and correct lifestyles (37). Previous studies have revealed that according to adverse pregnancy, childbirth, and neonatal outcomes caused by overweightness and obesity, greater care should be taken of these females (38,39).…”
Section: Discussionmentioning
confidence: 99%